CsxCo/Na-MOR Coating on Ceramic Monoliths for Co-Adsorption of Hydrocarbons Mixture and Selective Catalytic Reduction of NOx - Serra, Ramiro Marcelo (2023)
In this work, ceramic monoliths were coated with powders based on exchanged Cs and/or Co cations in Na-mordenite (MOR) zeolite. SEM images showed that zeolite particles fill the macropores of cordierite walls and form a continuous layer of approximately 40 μm with good adherence. XPS analysis revealed that Co and Cs are present on the film surface solely as Co2+ and Cs+ at exchange positions in zeolite. The monolithic structures were evaluated for the butane-toluene co-adsorption and SCR of NOx with hydrocarbon mixture as the reducing agent. The presence of alkali metal cations in the zeolitic lattice favored the adsorption capacity of both hydrocarbons, while cobalt cations provoked a decrease in the adsorbed amounts due to its weak interaction with the HCs. Breakthrough curves of butane adsorption showed a roll-up phenomenon, associated with a competitive adsorption effect generated from toluene presence. In the desorption process, it was observed that adsorbed toluene hindered the butane diffusion through mordenite channels, which released at higher temperatures (above 250 °C). Cs2CoM and Cs7CoM monoliths were more active than the CoM monolith for NO-SCR. The presence of Cs cations close to Co cations increased the hydrocarbons concentration around active sites at high temperatures, according to TPD results, promoting the reduction activity of NO.